The Role of the Government Through BUMDes in Improving the Welfare of Farmer Groups in South Coastal Area, West Sumatra - zulpardisyah zulpardisyah (Jurnal Indonesia Sosial Sains, 2025)
This study examines the role of village governments through Village-Owned Enterprises (BUMDes) in efforts to improve the welfare of farmer groups in South Pesisir Regency, West Sumatra. The background of the research is based on various problems faced by farmers in coastal areas, such as limited market access, inadequate infrastructure, uneven distribution of resources, and challenges in accessing modern agricultural capital and technology. These conditions have an impact on the low income of farmers and demand a strategic role from the government through BUMDes to optimize the potential of the village. Research Focus and Objectives. This research focuses on how the implementation of BUMDes can be developed optimally to:Provide access to capital and infrastructure facilities for farmer groups. Encourage diversification of agricultural businesses through training and capacity building of farmers. Improving coordination between village governments, BUMDes, and the community in managing sustainable agricultural businesses. The main goal is to develop a model of cooperation between the government and BUMDes that is able to improve the welfare of farmer groups through local economic empowerment and improving the quality of life of rural communities. The proposed research method involves a qualitative approach with case studies in several villages in the South Coast region. Data collection techniques include: In-depth interviews with village government officials, BUMDes administrators, and farmer groups. Direct observation in the field.vAnalysis of documents and secondary data related to the implementation of the BUMDes program and village development policies. Data analysis is carried out through systematic stages to get an in-depth picture of the role of BUMDes and its implications for community welfare. Theoretical and Practical ContributionsTheoretically, this research is expected to add references in the study of village management and management of BUMDes, as well as develop a comprehensive cooperation model between the government and the village community. Practically, the results of the research are expected to provide strategic recommendations to BUMDes managers and local governments to develop village development policies that are more responsive to the needs of farmer groups. Optimize the use of local resources to drive inclusive and sustainable economic growth. Thus, this proposal aims to provide innovative and applicable solutions in improving the welfare of farmers through the active role of village governments and BUMDes, so that it can be a reference for the development of village development programs in other regions.